Виявлення аномалій в SQL запитах - Степанов, В.; Мартовицький, В. О. (ХНУРЕ, 2019)
The paper deals with the possibility of using machine learning for tasks of classification of attacks not web system. A method for detecting anomalies in the form of SQL injection with the use of an autoencoder with Seq2Seq architecture has been developed, and the testing of the operation of the given transactions is performed.
Keywords: SQL-iн‘єкцiя; WEB-pесуpси; SQL; машинне навчання; автоенкодер